PENYULUHAN TENTANG BPJS KESEHATAN DI MUSHOLA NURUL IKHLAS RW 03 KELURAHAN KULIM TAHUN 2021 - Suryandartiwi, Wiwik; Salim, Agus; Faradhifa, Nadya (LPPM Universitas Awal Bros, 2022)
Since the enactment of the renewal law on the National Social Security System and the establishment of the Social Security Administering Body, health social security in Indonesia has been reformed and transferred entirely to BPJS Health given the lack of public interest and knowledge of the health insurance program provided by the National Social Security Administration. the government, its implementation is not optimal, especially in terms of health service administration and there are still many poor people who have not registered or become members of Health Social Security Agency in the National Health Insurance Program. In this article, the author describes the community service activities that have been carried out to increase public understanding of how to register for Health Social Security Agency and the importance of its use. Community service activities carried out in RW 03 Kulim Village, Kulim District used the method of material presentation, discussion and question and answer. As for the results of this community service activity, the public can understand how to register for Health Social Security Agency and the benefits of using which can be used to fulfill basic human needs, namely health